Program of social skills and Its impact on adults with intellectual disabilities - Franco, Maria da Glória; Garcês , Ana Isabel; Maia, Teresa (Aprender, 2025)
Social competence is a multidimensional concept that assumes a set of social behaviors appropriate to each context. Several social skills training programs have been developed to improve interpersonal relationships, but few target individuals with intellectual disabilities. This study assessed the impact of a social skills program designed for adults with mild or moderate intellectual disability, using a quasi-experimental design. The Social Interaction Skills Questionnaire, whose psychometric properties were analyzed for the Portuguese population, was administered in a pre-test and post-test format. Sixteen women aged between 20 and 37 years participated, evenly divided between an experimental group and a control group. The program implemented with the experimental group focused on conversational skills, assertiveness, problem solving, and basic social skills. The results indicate a significant increase in overall social skills, as well as specific improvements in conversational skills, problem solving, and basic social skills. Although not generalizable, the data suggests that the program has a positive impact.